Genetic effects of phenylpyrazoles on Citellus fulvus from biotopes of South Kazakhstan - Begymbetova, D. A.; Kolumbaeva, S. Zh.; Lovynskaya, A. V. (International Journal of Biology and Chemistry, 2012)
It was investigated of genotoxical effects of fipronil, that is widely used in Kazakhstan, on background rodents from South Kazakhstan biotopes, where widely used phenylpyrazoles insecticides. The frequency of chromosomal and genomic mutations in bone marrow cells of Citellus fulvus from Arys and Shardara areas were significantly higher (Р<0.01) than in rodents from Kazygurt area, that is furthest from the pesticide treatments. High level of chromatid aberrations are indicative for the presence of chemical mutagens. It was determined fipronil and it’s degradation to fipronil-sulfone metabolite in Citellus fulvus from biotopes of South Kazakhstan, where used phenylpyrazoles pesticides.